The covariance structure of East and West German incomes and its implications for the persistence of poverty and inequality - Biewen, Martin (Discussion papers, 2002)
Using data from the German Socio-Economic Panel (GSOEP), this paper analyzes the dynamics of equivalent income in Germany in the eighties and nineties. Special emphasis is given to the separation of permanent and transitory components, the persistence of transitory shocks and their implications for the persistence of poverty and income inequality. The results suggest that 52 to 69 percent of income inequality in West Germany were due to permanent differences between individuals and that poor individuals stayed in poverty for two years on average. In East Germany, the contribution of the permanent component to overall income inequality increased from 20 percent in 1990 to over 70 percent in 1998 and the persistence of poverty rose accordingly. The paper also looks at the special situation of population subgroups such as lone mothers, "double income no kids' households, couples with children and pensioners.
Keywords: Graue Literatur; Arbeitspapier